Effect of Lanthanum‐Aluminum Co‐Doping on Structure of Hafnium Oxide Ferroelectric Crystals - Zhenhai Li; Shuqi Tang; Tianyu Wang; Yongkai Liu; Jialin Meng; Jiajie Yu; Kangli Xu; Ruihong Yuan; Hao Zhu; Qingqing Sun; Shiyou Chen; David Wei Zhang; et al. (Advanced Science)
Abstract Hafnium oxide (HfO2)‐based devices have been extensively evaluated for high‐speed and low‐power memory applications. Here, the influence of aluminum (Al) and lanthanum (La) co‐doping HfO2 thin films on the ferroelectric characteristics of hafnium‐based devices is investigated. Among devices with different La/Al ratios, the Al and La co‐doped hafnium oxide (HfAlAO) device with 4.2% Al and 2.17% La exhibited the excellent remanent polarization and thermostability. Meanwhile, first principal analyses verified that hafnium‐based thin films with 4.2% Al and 2.17% La promoted the formation of the o‐phase against the paraelectric phase, providing theoretical support for supporting experimental results. Furthermore, a vertical ferroelectric HfO2 memory based on 3D macaroni architecture is reported. The devices show excellent ferroelectric characteristics of 22 µC cm−2 under 4.5 MV cm−1 and minimal coercive field of ≈1.6 V. In addition, the devices exhibit great memory performance, including the response speed of device can achieve 20 ns and endurance characteristic can achieve 1010 cycles.